A colaboração e as crenças na prática docente de professores de inglês para crianças na escola pública - Araújo, Marco André Franco de (2023)
The main objective of this research was to investigate collaborative practices and beliefs in the performance of English teachers for children in the public context. In addition, it was aimed at understanding both the theoretical and methodological perspectives that encompass teachers’ practices and their perceptions in relation to the collaborative practices. The investigation draws on studies related to the teaching of English for children, sociocultural theory, and its constructs - collaboration, interaction, and mediation in teacher education - and beliefs about teaching and learning foreign languages to children. From a methodological standpoint, it was carried out a case study between October 2019 and April 2021. The participants were four teachers who teach English in the public context of the Goiânia Municipal Education. As far as the data is concerned, it was used the following instruments: a) questionnaires; b) field notes and class observation; c) interviews; d) on-line collaborative sessions via Zoom platform; and e) narratives. From the data analysis, it was possible to infer that teachers both use beliefs about teaching ways that facitilate learning and beliefs about activities to children and promote meaningful experiences for their students. The analysis also indicate that contextual factors can change teachers' routine, leading them to shifts in their pedagogical practices. The discussion about collaborative sessions revealed that teachers, when participating in joint tasks, make use of strategies that mediate and facilitate such tasks. It was also able to identify the theoretical and methodological perspectives that permeate teachers' practice, such as choosing both methodologies – which are considered playful and bear collaborative tasks – and theoretical perspectives (e.g., teaching through repetition that little bring meaning to student learning). Teachers' perceptions about their participation in collaborative sessions, in turn, point to either change or maintenance of pedagogical practices. Thus, it may be argued that beliefs about the process of teaching and learning foreign languages for children and participation in collaborative practices in which teachers have the possibility to exchange experiences with their peers who work in the same context are important factors in the teachers’ education and that can help them in relation to their pedagogical practices for teaching English for children, that is, in the preparation of material, experiences exchange, and comparision of teaching contexts.